Impacto de los medios de comunicación audiovisuales en el desarrollo social y cultural en el Sector San José Tres de la Parroquia La Esperanza del Cantón Quevedo - Ayala Figueroa, Gladys Lorena (2019)
The new era of technology encompasses a very varied set of tools and equipment that flood the field of information and communication every year, but this is because everyone wants to be immersed in the latest advances in science, their Boom continues to increase every day and despite that there is concern in general terms of the creators of these technological tools, because we must always be innovating, this is the main objective of this report that audiovisual media provide possibilities for change so that the new Information and communication technologies enable the creation of a new socio-cultural space, promoting a productive development where each person has the possibility to create with a moving idea a knowledge transition process. Audiovisual media have been playing a great role in society for a long time, because their performance has to do with images, photographs and audio, and being didactic resources that with images and recordings serve to communicate messages then they are consecrating to that these and future generations can use them with total ease and in any area of life. Therefore, the audiovisual media is a channel that allows the transport of the desired contents in the construction of the messages here, many signs of different nature intervene and that help creativity, iconic signs that are images, verbal or linguistic signs that are the language with which the information is transmitted, nonverbal sound signs such as music, sound, noise and the combination of all these signs allows communication to flow, it is the case that a transmission can be made in real time, with different alternatives that benefit the entire community, then the inhabitants of the San José Tres sector of La Esperanza Parish will have the possibility of acquiring audiovisual media information workshops and strengthening the cultural development of their community